Pelatihan Kader Posyandu Remaja di Pesantren Mahasiswa Liwa’ul Haq Kelurahan Tondo Kecamatan Mantikurole: Youth Posyandu Cadre Training at the Liwa'ul Haq Student Islamic Boarding School, Tondo Village, Mantikurole District - Anna Veronica Pont; Olkamien Jesdika Longulo; Mardiani Mangun (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
Youth health services at posyandu can facilitate adolescents in understanding and preventing adolescent health problems. The village of Tondo does not yet have a youth posyandu. The number of adolescents in the district of Tondo: 1267 young women and 1170 boys. Community service aims to determine the knowledge and skills of adolescents in providing youth posyandu services at the Liwa'ul Haq pasantren, Tondo sub-district. The community service method is providing training for youth posyandu cadres at the Liwa'ul Haq Islamic boarding school, Tondo sub-district, training participants for 15 youths. Cadre training is divided into three stages, namely: the first is education (theory), the second is practice/role play in the classroom and the third is the practice of serving 5-table youth posyandu (stages) to adolescents. The training was carried out for 3 days by the Poltekkes Service Team of the Ministry of Health Palu in partnership with the Talise and Ponpes Liwa'ul Haq Health Center, with 15 participants. Prior to training, a pretest was conducted. After the training Posttest results the knowledge and skills of adolescents increased. It is hoped that the Head of the Talise Health Center, the Coordinator of the Youth Posyandu service will continue to fall down for the preparation of Posrem services at the Liwa'ul Haq Islamic Boarding School.   ABSTRAK  Layanan kesehatan remaja di posyandu dapat memfasilitasi remaja dalam memahami dan mencegah permasalahan kesehatan remaja. Kelurahan Tondo belum memiliki posyandu remaja. Jumlah remaja di keluruhan Tondo: remaja putri 1267 dan remaja putra 1170. Pengabdian masyarakt bertujuan diketahuinya pengetahuan dan ketrampailan remaja dalam memberikan pelayanan posyandu remaja di pasantren Liwa’ul Haq kelurahan Tondo. Metode pengabdian masyarakat adalah memberikan pelatihan kader posyandu remaja di Pasantren Liwa’ul Haq kelurahan Tondo, peserta pelatihan 15 orang remaja. Pelatihan kader dibagi menjadi tiga tahapan, yaitu: pertama adalah edukasi (teori), kedua adalah praktik/ role play di kelas dan ke tiga praktik pelayanan posyandu remaja 5 meja (tahap) kepada remaja. Pelatihan dilaksanakan selama 3 hari oleh Tim Pengabdian Poltekkes Kemenkes Palu bermitra dengan Puskesmas Talisedan Ponpes Liwa’ul Haq, peserta berjumlah 15 orang. Sebelum pelatihan dilakukan pretes.  Setelah pelatihan Hasil Posttest pengetahuan dan ketrampilan remaja meningkat. Diharapakan Kepala Puskesmas Talise, Koordinator pelayanan Posyandu remaja  tetap fallow up untuk persiapan pelayanan  Posrem di Ponpes Liwa’ul Haq.